2002
DOI: 10.4319/lo.2002.47.1.0295
|View full text |Cite
|
Sign up to set email alerts
|

UV‐induced pigmentation in subarctic Daphnia

Abstract: The distribution of the planktonic crustacean Daphnia and the occurrence of ultraviolet (UV)‐protective melanin pigmentation in its body wall were studied in relation to the UV transparency in subarctic ponds and lakes in Finnish Lapland. In shallow ponds, Daphnia only occurred in those with sufficient amounts of UV‐screening dissolved organic matter. The highest pigment concentration was found in these Daphnia and in populations that occurred in lakes with low organic carbon content (<2 mg L−1). Pigment synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 15 publications
3
58
0
Order By: Relevance
“…With respect to copepods, the UV radiation in my studies was not lethal, although nonlethal UV radiation may affect other properties, such as growth and reproduction. Hence, due to their plasticity in photo-protective pigmentation, copepods and possibly some species of Daphnia (Hessen 1996, Rautio andKorhola 2001) may be predicted to be more successful than many other zooplankton groups, as the ozone hole continues to grow (Pieintz and Vincent 2000). This notion is in line with recent field experiments showing that altered UV radiation affected the taxonomic composition by reducing abundances of some organisms, while leaving others, among them pigmented copepods, unaffected (Vinebrooke and Leavitt 1999).…”
Section: Discussionmentioning
confidence: 57%
“…With respect to copepods, the UV radiation in my studies was not lethal, although nonlethal UV radiation may affect other properties, such as growth and reproduction. Hence, due to their plasticity in photo-protective pigmentation, copepods and possibly some species of Daphnia (Hessen 1996, Rautio andKorhola 2001) may be predicted to be more successful than many other zooplankton groups, as the ozone hole continues to grow (Pieintz and Vincent 2000). This notion is in line with recent field experiments showing that altered UV radiation affected the taxonomic composition by reducing abundances of some organisms, while leaving others, among them pigmented copepods, unaffected (Vinebrooke and Leavitt 1999).…”
Section: Discussionmentioning
confidence: 57%
“…Black eumelanin is a common pigment in artic Daphnia spp. (Hebert & Emery 1990, Hessen & Sørensen 1990, Hobaek & Wolf 1991, Rautio & Korhola 2002, Hansson et al 2007), but has not been reported for other zooplankton. In the present study, we measured melanin in 4 species of zooplankton species (Daphnia middendorffiana, Scapholeberis mucronata, Artemiopsis stefanssoni and Branchinecta paludosa).…”
Section: Range Of Pigments and Maas In High-latitude Zooplanktonmentioning
confidence: 96%
“…More recent studies have also concluded that pigmented individuals survive better than pale individuals when exposed to UV radiation (Hairston 1976, Hessen 1996, and that there is a strong seasonal variation in pigment content. Subarctic Daphnia umbra synthesize melanin only during summer months, beginning immediately after ice-out (Rautio & Korhola 2002), and alpine copepods peak in their mycosporine-like amino acid (MAAs) concentrations during the open-water period (Tartarotti & Sommaruga 2006, Persaud et al 2007). Pigments and the colourless MAAs in zooplankton are mostly considered to be UV photoprotectants (Perin & Lean 2004), acting together with other photoprotectants such as antioxidants and with behavioural responses such as vertical migration.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the saline and brackish aquatic ecosystems of the Atacama desert and in southern Patagonia have a wide gradient of concentrations of DOC (De los Ríos, 2003). Consequently, it is reasonable to predict that there would be marked differences in the energy spent by individuals in developing photo-protection that would affect fecundity, individual growth, and absolute abundance of various populations (Rautio, 1998;Winder, 2001;Rautio & Korkhola, 2002a, 2002b. Indeed, integrated laboratory and field studies involving an array of brine shrimp natural sites and investigating the effect of variation in levels of protection provided by different concentrations of DOC protection against UVR damage, may be an important line of research to pursue in Chile from the sandpoint of conserving natural stocks of brine shrimp at a time of major changes in atmospheric conditions of planet Earth.…”
Section: Future Directionsmentioning
confidence: 99%